السجع في الأفعال الكلامية الإنجازية فى مسلسل كرتون محسن و محاسن لتأليف قناة يوتوب جمعية نمآء الخيرية (الدراسة براغماتية لجون رابيرت سيرلى) - Indriani Purnama Sari, Luci (Journal of Arabic Language and Literature (ALLAIS), 2023)
This study discusses the types and functions of illocutionary speech acts in the cartoon series Muhsin wa Mahasin. The purpose of this study is to describe the types and functions of illocutionary speech acts contained in the cartoon series Muhsin wa Mahasin. The research method used in this research is qualitative with literature study. The data collection technique used in this research is the listening method, the data collection technique using reference materials and the data analysis technique using the equivalent method which is supported by the SPEAKING speech component. The results of the analysis in this study are that in assertive speech acts the researcher finds speeches stating with affirmation, expressing with anxiety and complaining to get help. In directive speech acts, the researcher finds utterances of suggesting, commanding, pleading and advising. In commissive speech acts, the researcher finds utterances in the form of promises and refusals. And in expressive speech acts the researcher found utterances in the form of thanking, apologizing, praising, worried and surprised. The function of speech acts that the researchers found is a competitive function in which there is an utterance that functions to command and ask the speech partner, in the convival function the researcher finds speech with a polite and friendly attitude, namely an utterance that functions to thank, congratulate and greet, collaborative function The researcher found utterances with the intention of working together, namely utterances which functioned to express and conflictive functions.